Setting the optimal threshold of NT‐proBNP and BNP for the diagnosis of heart failure in patients over 75 years - Emmanuelle Berthelot; Minh Tam Bailly; Xenia Cerchez Lehova; Manel El Blidi Rahmani; Rahil Bounab; Nathan Mewton; John E. Dobbs; Remy Mas; Marie Frank; Nicolas Lellouche; Marion Paclot; Patrick Jourdain (ESC Heart Failure, 2024)
Abstract Aims Diagnosing acute heart failure (AHF) remains particularly challenging in older patients. Natriuretic peptides are recommended as valuable diagnostic tools in this context. This study aims to establish the diagnostic thresholds of B‐type natriuretic peptide (BNP) and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) for AHF in patients aged over 75 years, both with and without co‐morbidities. Methods and results In this retrospective longitudinal multicentre cohort study, data were gathered from 12 071 hospitalized patients aged 75 years or older, presenting with acute dyspnoea and undergoing BNP or NT‐proBNP measurement within 48 h of admission across 10 Assistance Publique‐Hôpitaux de Paris facilities between 2011 and 2022, encompassing geriatrics, cardiology, and pulmonology departments. Final diagnoses were categorized using ICD‐10 criteria as either AHF or other acute respiratory conditions such as COPD exacerbation, pulmonary embolism, and pneumonia. The mean (SD) age of the population was 84.0 (80.0, 89.0) years, with 52.7% being female. Out of these, 7946 (65.8%) were diagnosed with AHF upon discharge. For NT‐proBNP, the identified ‘optimal’ threshold for diagnosing AHF was 1748 ng/L, with a positive predictive value (PPV) of 84%. Among patients aged over 85 years, a threshold of 2235 pg/mL for NT‐proBNP was associated with an 84% PPV. In patients with atrial fibrillation (AF), a threshold of 2332 pg/mL for NT‐proBNP demonstrated a PPV of 90% for AHF diagnosis. Additionally, in patients with an estimated glomerular filtration rate (eGFR) < 30 mL/min, a threshold of 3474 pg/mL for NT‐proBNP yielded a 90% PPV for AHF diagnosis. In male patients, a threshold of 1800 pg/mL showed an 85% PPV for AHF diagnosis, while in patients with obesity, a threshold of 1375 pg/mL demonstrated an 85% PPV for AHF diagnosis. Conclusions In older patients, we found significant effects of co‐morbidities on natriuretic peptides results, particularly in patients over 85 years old, older patients with abnormal renal function, obesity, and atrial fibrillation. Despite the consideration of those co‐morbid conditions, NT‐proBNP and BNP level continue to demonstrate utility in the diagnosis of AHF in older patients.